Genome scan identifies flowering-independent effects of barley HsDry2.2 locus on yield traits under water deficit - Merchuk-Ovnat, Lianne (Journal of experimental botany, 2018)
Increasing crop productivity under conditions of climate change requires the identification, selection, and utilization of novel alleles for breeding. In this study, we analysed the genotype and field phenotype of the barley HEB-25 multi-parent mapping population under well-watered and water-limited environments for two years. A genome-wide association study (GWAS) for genotype × environment interactions was performed for 10 traits including flowering time (heading time, HEA) and plant grain yield (PGY). Comparison of the GWAS for traits per se (i.e. regardless of the environment) with a study for quantitative trait loci (QTLs) × environment interactions (Q×E), indicates the prevalence of Q×E mostly for reproductive traits. One Q×E locus on chromosome 2, Hordeum spontaneum Dry2.2 (HsDry2.2), showed a positive and conditional effect on PGY and grain number (GN). The wild allele significantly reduced HEA; however, this earliness was not conditioned by water deficit. Furthermore, BC2F1 lines segregating for the HsDry2.2 locus showed that the wild allele conferred an advantage over the cultivated allele in PGY, GN, and harvest index, as well as modified shoot morphology, a longer grain-filling period, and reduced senescence (only under drought). This suggests the presence of an adaptation mechanism against water deficit rather than an escape mechanism. The study highlights the value of evaluating wild relatives in search of novel alleles and provides clues to resilience mechanisms underlying crop adaptations to abiotic stress